2007
DOI: 10.3113/fai.2007.1194
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal Tendon Subluxation Repair With an Indirect Fibular Groove Deepening Technique

Abstract: An indirect groove deepening technique is an effective way of treating peroneal tendon dislocation with good results. Patients with Worker's Compensation claims or other associated pathology have poorer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 16 publications
2
32
0
5
Order By: Relevance
“…5 Both aspects promote a fast rehabilitation for the patient. 15 There seems to be a variety of factors influencing the outcome. Ogawa et al 15 reported inferior results with their technique in patients with additional peroneal tendon tears or in patients with workers' compensation claims.…”
Section: Discussionmentioning
confidence: 98%
“…5 Both aspects promote a fast rehabilitation for the patient. 15 There seems to be a variety of factors influencing the outcome. Ogawa et al 15 reported inferior results with their technique in patients with additional peroneal tendon tears or in patients with workers' compensation claims.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, other authors have advocated an indirect groove-deepening technique by burring the cancellous bone from under the cortex, starting at the tip of the fibula, followed by direct impaction of the cortex. 2,7,10,13,14,18 Shawen and Anderson 14 described cannulating the fibula using a biotenodesis system followed by tamping the posterior cortex down without making an osteotomy in the posterior fibula. Without osteotomizing of the fibula, however, additional force is needed to tamp down the posterior cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This preserves the floor of the groove, which is tamped down into the drilled tunnel, thus deepening it. 40,41 …”
Section: Pathological Conditionsmentioning
confidence: 99%